2020
DOI: 10.1007/s11524-019-00404-x
|View full text |Cite
|
Sign up to set email alerts
|

Violence and Emergency Department Use among Community-Recruited Women Who Experience Homelessness and Housing Instability

Abstract: Women who experience housing instability are at high risk for violence and have disproportionately high rates of emergency department (ED) use. However, little has been done to characterize the violence they experience, or to understand how it may be related to ED use. We recruited homeless and unstably housed women from San Francisco shelters, free meal programs, and single room occupancy (SRO) hotels. We used generalized estimating equations to examine associations between violence and any ED use (i.e., an E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 50 publications
2
20
0
Order By: Relevance
“…HIV-positive persons were oversampled to accomplish HIV-related aims of the original study. Previous research suggests these participants were similar to HIV-negative participants across a range of measured variables (Riley et al 2020 ). Participants were remunerated $40 for each study interview.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…HIV-positive persons were oversampled to accomplish HIV-related aims of the original study. Previous research suggests these participants were similar to HIV-negative participants across a range of measured variables (Riley et al 2020 ). Participants were remunerated $40 for each study interview.…”
Section: Methodsmentioning
confidence: 69%
“…Among studies that report violence against unhoused and unstably housed women, few report specifically on weapon-involved violence. Among those that have, a study of San Francisco women living in unstable housing conditions found 48% had experienced physical violence without a weapon and 18% had experienced physical violence with a weapon in the six months prior to interview (Riley et al 2020 ). Factors specifically associated with gun and other weapon-involved violence against unstably housed women are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Relatedly, our analysis also revealed that media reinforced ideas about “appropriate” use of the ED, for example, during our search of articles related to the Northern Regional site, we found media headlines such as “Too Many Patients at UHNBC” [ 28 ] and “Unnecessary hospital trips clogging up Fort St. John ER” [ 29 ]. Although overcapacity and overcrowding at these EDs are factual realities [ 30 ], the broader contexts of people’s lives that influence their use of EDs (e.g., inadequate and unsafe housing) tends to be overlooked [ 31 33 ]. Headlines such as these imply that patients have the choice to visit the ED or not, and this is not necessarily true for everyone.…”
Section: Resultsmentioning
confidence: 99%
“…There may also some parallels to the literature on schizophrenia where some have argued that the onset of psychosis can be a traumatic event that leads to PTSD (Mueser et al, 2010). Further, various studies have found that homelessness is associated with high rates of death, injury, and illness (Gorman & Rowan, 2019; Nilsson et al, 2018; Riley et al, 2020; Schinka et al, 2016; Tong et al, 2019). It may also be that other PTEs are likely to occur, whereas one is homeless so that homelessness becomes a context in which one might experience a Criterion A trauma.…”
Section: Discussionmentioning
confidence: 99%
“…In the Diagnostic and Statistical Manual of Mental Disorders‐Fifth Edition ( DSM‐5 ; American Psychiatric Association, 2013), the precipitating event or stressor is known as Criterion A and involves direct or indirect exposure to “death, threatened death, actual or threatened serious injury, or actual or threatened sexual violence.” The experience of homelessness may qualify for Criterion A as illustrated by comments made by individuals experiencing homelessness, such as “I thought I was going to die” (Law, 2019) and “My fear is being found on the street, but no one knowing how to help me or who I am” (Song et al, 2007). There are also many studies that have found homelessness is linked to substantially elevated rates of health morbidities, physical and sexual victimization, and mortality (Gorman & Rowan, 2019; Nilsson et al, 2018; Riley et al, 2020; Schinka et al, 2016; Tong et al, 2019).…”
Section: Introductionmentioning
confidence: 99%